Influence of Natural Oxygenation of Baltic Proper Deep Water on Benthic Recycling and Removal of Phosphorus, Nitrogen, Silicon and Carbon - Hall, Per O. J.; Almroth Rosell, Elin; Bonaglia, Stefano; Dale, Andrew W.; Hylén, Astrid; Kononets, Mikhail; Nilsson, Madeleine; Sommer, Stefan; van de Velde, Sebastiaan; Viktorsson, Lena (Frontiers in Marine Science, 2017)
At the end of 2014, a major Baltic inflow (MBI) brought oxygenated, salty water into the Baltic proper and reached the long-term anoxic Eastern Gotland Basin (EGB) by March 2015. In July 2015, we measured benthic fluxes of phosphorus (P), nitrogen (N) and silicon (Si) nutrients and dissolved inorganic carbon (DIC) in situ using an autonomous benthic lander at deep sites (170-210 m) in the EGB, where the bottom water oxygen concentration was 30-45 µM. The same in situ methodology was used to measure benthic fluxes at the same sites in 2008-2010, but then under anoxic conditions. The high efflux of phosphate under anoxic conditions became lower upon oxygenation, and turned into an influx in about 50 % of the flux measurements. The C:P and N:P ratios of the benthic solute flux changed from clearly below the Redfield ratio (on average about 70 and 3-4, respectively) under anoxia to approaching or being well above the Redfield ratio upon oxygenation. These observations demonstrate retention of P in newly oxygenated sediments. We found no significant effect of oxygenation on the benthic ammonium, silicate and DIC flux. We also measured benthic denitrification, anammox and dissimilatory nitrate reduction to ammonium (DNRA) rates at the same sites using isotope-pairing techniques. The bottom water of the long-term anoxic EGB contained less than 0.5 µM nitrate in 2008-2010, but the oxygenation event created bottom water nitrate concentrations of about 10 µM in July 2015 and the benthic flux of nitrate was consistently directed into the sediment. Nitrate reduction to both dinitrogen gas (denitrification) and ammonium (DNRA) was initiated in the newly oxygenated sediments, while anammox activity was negligible. We estimated the influence of this oxygenation event on the magnitudes of the integrated benthic P flux (the internal P load) and the fixed N removal through benthic and pelagic denitrification by comparing with a hypothetical scenario without the MBI. Our calculations suggest that the oxygenation triggered by the MBI in July 2015, extrapolated to the basin-wide scale of the Baltic proper, decreased the internal P load by 23% and increased the total (benthic plus pelagic) denitrification by 18%.